The moderating role of income diversification on the relationship between intellectual capital and bank performance evidence from Viet Nam - Dat T Nguyen; Tu DQ Le; Son H Tran (Cogent Business & Management, 2023)
This study investigated whether income diversification moderates the relationship between Intellectual Capital and bank performance in Vietnamese commercial banks period 2007-2020 using the system generalised method of moments (GMM)." The results indicate that the value added intellectual coefficient (VAIC) and its components ("human capital efficiency (HCE), " capital employed efficiency (CEE), and "structural capital efficiency (SCE)) have positive effects on bank performance. Second, the study examines that income diversification (ID) has a negative and considerable impact on bank performance. Finally, the findings show that income diversification, as a moderating element, lowered the overall impact of IC (Value Added Intellectual Capital (VAIC)) efficiency on bank performance. The role of income diversification in modulating the link between the distinct components of VAIC (HCE, SCE and CEE). While revenue diversification improved the influence of SCE on bank performance, it weakened the impact of HCE. Furthermore, income diversification had little effect on bank performance in terms of mitigating the effects of CEE. Therefore, this finding highlights the contribution by suggesting that non-traditional banking activities influence the relationship between Intellectual Capital and bank performance in Vietnam
Keywords: 650; Vietnam; intellectual capital; bank performance; income diversification